Gun crusaders : the NRA's culture war - Melzer, Scott (New York University Press, 2009)
"Nothing conjures up images of the American frontier and a pick-yourself-up-by-the-bootstraps view of freedom and independence quite like guns. Gun Crusaders is a fascinating inside look at how the four-million member National Rifle Association and its committed members come to see each and every gun control threat as a step down the path towards gun confiscation, and eventually socialism. Enlivened by a rich analysis of NRA materials, meetings, leader speeches, and unique in-depth interviews with NRA members, Gun Crusaders focuses on how the NRA constructs and perceives threats to gun rights as one more attack in a broad liberal cultural war. Scott Melzer shows that the NRA promotes a nostalgic vision of frontier masculinity, whereby gun rights defenders are seen as patriots and freedom fighters, defending not the freedom of religion, but the religion of individual rights and freedoms"-Resumé vydavatel
Keywords: National Rifle Association of America; střelné zbraně -- Spojené státy americké; soukromé vlastnictví; ranged weapons -- United States; private ownership; elektronické knihy; monografie; electronic books; monographs